1998
DOI: 10.1144/gsl.sp.1998.139.01.11
|View full text |Cite
|
Sign up to set email alerts
|

Ecological interaction and sediment transport on an intertidal mudflat I. Evidence for a biologically mediated sediment-water interface

Abstract: Using biological, chemical and physical data, evidence of biologically mediated cohesive sediment dynamics is presented for an intertidal mudflat in the Humber Estuary, UK. The data suggest that in excess of 98% of sediment fluxes to the sediment bed on the mudflat are subject to resuspension, forming a bedload that is important in generating the shear stress required to erode the sediment bed. Benthic micro-algae photosynthesize and are grazed by macro-heterotrophs within this 300-3000 #m deep dynamic surface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 28 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…Indeed, Edgar & PickettHeaps 11984) concluded that no large amounts of polysaccharide have to be secreted for motihty, hence other factors, such as overflow metabolism, may enhance secretion of polysaccharide during daytime emersion. Ruddy et al (1998) calculated that the accumulation of carbohydrate in the sediment during emersion may well be the result of excess carbon fixation due to nitrogen limitation. There may be additional benefits in secretion of polysaccharides, such as protecting cells against resuspension or desiccation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Edgar & PickettHeaps 11984) concluded that no large amounts of polysaccharide have to be secreted for motihty, hence other factors, such as overflow metabolism, may enhance secretion of polysaccharide during daytime emersion. Ruddy et al (1998) calculated that the accumulation of carbohydrate in the sediment during emersion may well be the result of excess carbon fixation due to nitrogen limitation. There may be additional benefits in secretion of polysaccharides, such as protecting cells against resuspension or desiccation.…”
Section: Discussionmentioning
confidence: 99%
“…The excretion of EPS plays a role in the movement of epipelic benthic diatoms (Edgar & PickettHeaps 1983) and allows the organisms to adhere to sediment surfaces (Wang et al 1997). EPS-production may also be controlled by nutrient availability, for instance when the organisms grow under unbalanced conditions (Ruddy et al 1998), a situation likely to occur in intertidal environments (Flothmann & Werner 1992). The presence of diatom biofilms increases the stability of the sediment surface (Kornman & de Deckere 1998, Paterson 1989) and can have a profound effect on the morphodynamics of mudflats (Dyer 1998.…”
Section: Introductionmentioning
confidence: 99%
“…Tidal flows have been at the center of extensive investigations on tidal-flat sedimentation, and their role is commonly recognized to be of major importance in the long term evolution of marine estuaries and tidal-flats (Ridderinkhof 1997;Wood et al 1998). Much research has also been directed at the interplay of biological and physical aspects of sediment transport on tidal-flats (e.g., Bell et al 1997;Widdows et al 1998;Ruddy et al 1998). While it is readily acknowledged that physical factors influence tidal-flat sedimentation (Paterson et al 1990), predicted trends of erosion and deposition that may be influenced strongly by biological controls including surface vegetation (Frostick and McCave 1979), binding diatoms (Paterson 1989), attached molluscs (Meadows et al 1998) and burrowing infauna (Meadows et al 1990).…”
Section: Introductionmentioning
confidence: 99%